Dokumen kontrak : inspection, servicing, preventive and breakdown maintenance of fire protection and auxiliary equipment at Universiti Teknologi Malaysia Skudai Johor (package B) - Universiti Teknologi Malaysia; Bersia Engineering Services (M) Sdn. Bhd. (Skudai : Universiti Teknologi Malaysia, 2006)
PRZSL